2020
DOI: 10.1088/1755-1315/468/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of secondary metabolites of Trichoderma spp. in inhibiting Phytophthora palmivora growth in cacao (Theobroma cacao L.)

Abstract: Secondary metabolites are organic compounds produced by microorganisms or plants which are not directly involved to development and reproduction. The secondary metabolites produced by Trichoderma spp. are antibiotic compounds, enzymes, toxins, and hormones that inhibit the growth of plant pathogens. Phytophthora palmivora is a pathogen that causes black pod, leaf blight, and stem canker in cacao, which potentially reduce production up to 40%. This study was aimed to determine the inhibitory effect of Trichoder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Moreover, Trichoderma spp. could inhibit the growth of pathogenic fungi by secreting antibiotics and volatile organic compounds ( Harni et al., 2020 ). Here, we also found that strain N4-3 exhibited a remarkable ability to inhibit the growth of Foc TR4 mycelia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Trichoderma spp. could inhibit the growth of pathogenic fungi by secreting antibiotics and volatile organic compounds ( Harni et al., 2020 ). Here, we also found that strain N4-3 exhibited a remarkable ability to inhibit the growth of Foc TR4 mycelia.…”
Section: Discussionmentioning
confidence: 99%
“…They can parasitize the hyphae of pathogenic fungi and produce cell wall-degrading enzymes, ultimately leading to the death of the pathogenic fungi. Additionally, Trichoderma can also inhibit the growth of plant pathogens by producing secondary metabolites and volatile organic compounds that have antagonistic activity ( Harni et al., 2020 ; Lv et al, 2023 ). For instance, the active metabolite gliotoxin, isolated from the culture broth of Trichoderma virens HZA14, was found to completely inhibit the growth of Phytophthora capici mycelium when added to PDA at a concentration of 5.0 μg/mL ( Tomah et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Propagation technique of Trichoderma spp. secondary metabolite according to methods of [18] which used vegetative and fermentative media. The composition of vegetative media was glucose, potato, Na2HPO4, NaH2PO4, Urea, KCl, MgSO4, Thiamin HCl, MnSO4, ZnSO4, FeSO4, and distilled water.…”
Section: Mass Propagation Of Secondary Metabolite Trichoderma Sppmentioning
confidence: 99%
“…Trichoderma suspension made from agar slanted (10 ml), plus 2 ml of sterile physiological NaCl solution. The cultures were then incubated at 28 °C using an orbital shaker (200 rpm; 48 hours) [18]. After the vegetative stage completed, a fermentative stage aimed to produce secondary metabolites of T. virens LP1 and T. amazonicum LP3 was performed.…”
Section: Mass Propagation Of Secondary Metabolite Trichoderma Sppmentioning
confidence: 99%